Kombinasi Kriptografi Modern Dalam Keamanan Pesan Teks - Dhea Agustina Akmal; Dicha Mutia Dhani; Febby Syahila (Saturnus: Jurnal Teknologi dan Sistem Informasi, 2024)
In the rapidly advancing digital era, information security has become a crucial aspect in maintaining the confidentiality, integrity, and authenticity of data. This article discusses the relationship between information system auditing and the use of modern cryptographic combinations in securing text messages. Information system auditing serves as an evaluation mechanism to ensure that security policies, procedures, and standards are correctly and consistently applied. On the other hand, modern cryptography provides advanced encryption technology that protects text messages from unauthorized access and manipulation. By combining these two approaches, we can create a robust framework for securing text messages, ensuring that data remains safe and protected during transmission and storage. Research results indicate that integrating information system auditing with modern cryptographic techniques significantly enhances the security and reliability of information systems.